Distance Strategies for Arabic Learning/إستراتيجيات تعليم اللغة العربية عن بعد - Muhammad Arifin; Ahmad Muhammad Husni (Jurnal Al-Maqoyis, 2021)
Active learning strategies are all forms of learning that allow students play an active role in the learning process. There is a covid pandemic 19 can hinder its implementation, such as delivery methods, quotas and networks Internet. In this case the tutors must determine the right strategy in learning delivery of Arabic language matrices such as the four maharahs online. The formulation of the problem in this study is to explore language learning strategies distance Arabic on the four aspects of language skills. And the goal in this research is to find out how the strategy is implemented. This research method uses a qualitative approach by using Qualitative descriptive method with the type of field research on a matrix scale consisting of from analysis with data collection tools in the form of observations, interviews, documentation. The results of the study show that the learning strategies used in listening skills is a PAKEM strategy with the samiyah syafahiyah method, in the third subject using the method correctly according to the aspects of listening skills while the other subjects tend to learn skills read. The learning strategies of speaking skills applied are: PAKEM strategy with direct method, the third subject using the method correctly according to the aspect of listening skills, while the other subjects tend to learn reading skills. Learning strategies on reading skills using the PAKEM strategy by the third tutor, while the other tutors use the inquiry method. The three tutors use the method qiraah jahriya. The Arabic language learning strategy for writing skills that is applied is the PAKEM strategy for the third tutor, and the others using inquiry. All tutors use the imla masmu and imla manqul methods.